Improving Student Soft Skills Through Seminars, Training, And FGDs Carried Out In Blended Learning - Maghfirah, Nuril (Institut Agama Islam Negeri (IAIN) Kudus, 2022)
Students must have qualified soft skills according to their scientific fields and the needs of stakeholders so that they have high competitiveness. Students of the Islamic Community Development Study Program are required to have one type of soft skills, namely communication. The main thing is public speaking and negotiation skills. These abilities must be continuously honed and improved. This study aims to determine the improvement of student soft skills through a series of activities in the form of seminars, training, and Focus Group Discussions (FGD). The object of the study was 30 seventh-semester students of the Islamic Community Development Study Program of IAIN Kudus. A series of activities in the form of seminars, training, and FGDs through in blended learning for five consecutive days with a total of 40 JPL along with evaluations on each material. This study used a quantitative approach with t-tests (pretest and posttest) using SPSS version 26. Based on the results of the t-test, the mean of pretest (67.57) and posttest (73.30) was obtained and a significancy of <0.05. These results show that seminars, training, and FGDs through blended learning have a significant effect on improving student soft skills.